Management development through cultural diversity - Ronnie Lessem (Routledge, 1998)
This stimulating, clearly written and well-structured text is a comprehensive introduction to the principles of management and organisational behaviour, as well as a corrective to the eurocentric bias of most management texts. It develops a trans-cultural perspective which draws on insights from across the world to examine different management styles, cultures and stages of business development. Contents include: * Orientation * Primal Management - Western including America * Rational Management - Northern including Scandinavia * Developmental Management - Eastern including Japan * Metaphysical Management - Southern including South Africa * Developing yourself as a manager Each section examines core management theory and literature, cultural orientation and related prominent theories. The numerous case studies use appropriate examples from a wide range of international organisations. The uniquely wide-ranging perspective make this a valuable text for all those interested in general management, international business, organisational behaviour and corporate strategy.
Keywords: 650